Against Proportional Punishment - Kolber, Adam J. (2013)
Many criminal defendants are held in detention while they await trial. Though conditions in pretrial detention are much like those in prison, detention is technically not punishment. Since detainees are merely accused of crimes, they are presumed innocent.' Their detention is not intended to punish them, and so, the Supreme Court has said, it is not punishment at all. Rather, detention is a means of promoting public safety, reducing witness intimidation, and preventing people accused of crimes from fleeing before trial. Nevertheless, defendants who are convicted generally receive credit at sentencing for time served in pretrial detention. An offender who deserves two years of incarceration as punishment will have his sentence cut in half if he has already spent one year in detention. Such offsets appear to conflict with principles of proportional punishment. Taken literally, giving credit for time served leads us to systematically underpunish detainees by reducing their punishment by time spent unpunished. To unlock the mystery of credit for time served, defenders of proportionality need to square the widely held view that offenders should receive credit for time served with the widely held view that punishment should be proportional to blameworthiness